Teacher Centered Versus Student Centered Strategies for Undergraduate Students - Fatima, Sadaf (Pakistan Armed Forces Medical Journal, 2022)
Objective: To compare the student-centred learning strategies with teacher-centred strategies in developing adult learning principles for medical students.Study Design: Quasi-experimental study.Place and Duration of Study: Ziauddin Medical College and Jinnah Medical & Dental College, Karachi, Nov 2017 to Oct 2018.Methodology: The study participants included first and second-year medical students. They were divided into two groups. One group of students was recruited from a medical college having a hybrid curriculum through problem based learning and lectures. The other students were recruited from a college following a traditional curriculum through only teacher-centred strategies and lectures. The comparison between the two groups of students was based on adult learning principles. A questionnaire including 17 items from the principles of adult learning scale (PALS) was given to medical students. Out of 17 items from the principles of adult learning scale, 13 were related to student learning, and four were regarding teacher instruction. The students were asked to determine the teaching practices promoting the development of adult learning principles on a Likert scale from 0-5.Results: In the learning section, the medical students having student-centred learning strategies had 28.16 ± 10.98 scores compared to students with teacher-centred strategies with a score of 33.73 ± 12.66 on the principles of adult learning scale. In the teacher instruction section, the score was 13.81 ± 3.76 in students with learner-centered strategies and 14.76 ± 3.79 in students with teacher-centred strategies.Conclusion: The teacher-centred learning strategies promote the development of adult learning principles better than the student-centred strategies in medical students.